Implementasi Nilai Sila Pancasila "Kerakyatan yang Dipimpin oleh Hikmat Kebijaksanaan dalam Permusyawaratan/Perwakilan" dalam Kegiatan Kepramukaan di SMK Islam Anharul Ulum Kecamatan Kademangan - Siti Hajarmaryam; Dwi Retnani Srinarwati; Cicik Pramesti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Implementation of the fourth principle of Pancasila in scouting activities has an important role in shaping the character of students. The fourth principle of Pancasila teaches students to apply the principles of democracy, deliberation and wise leadership. This study seeks to explain how the values of Pancasila are applied in practice people which is guided by wisdom in deliberation and representation in scouting activities at Anharul Ulum Islamic Vocational School, Kademangan District. This study employs a qualitative approach utilizing descriptive methods. Data were obtained through interviews and observations and documentation involving Scout leaders, the Standing Council, and class X TO 1 students. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results of the research show that scouting activities at Anharul Ulum Islamic Vocational School have succeeded in implementing the fourth principle value through consensus deliberation, leadership training, discipline in decision making, and cooperation in mutual cooperation. However, there are still obstacles in optimizing student participation in deliberations and awareness of the importance of wisdom in leadership. In conclusion, scouting is an effective forum for instilling the values of democracy and togetherness, so there is a need for further support from the school to increase the implementation of Pancasila values in extracurricular activities.